Agriculture in India and Pakistan, 1990-95: productivity and crop mix - Kurosaki, Takashi (1999)
In the context of economic liberalisation during the 1990s, we investigate the performance of agriculture in India and Pakistan, 1900-95, from historical and comparative perspectives. Based on a new data set that corresponds to the current border, we show a distinct turnaround at the time of partition in 1947 - the stagnant performance of agriculture in India and Pakistan during the colonial period was turned into a sustained growth since 1947, with a stronger performance in India especially in terms of per capita food production. Empirical investigation in this paper gives support to the view that institutional changes have significant effects on agricultural production in India and Pakistan. Farmers have responded to changes in institutions and policies, adjusting their crop mix and production technology. - Reproduced
Keywords: Agriculture - Pakistan; Agriculture - India; Agriculture